Relationship Between Pressure Pain Threshold and Coping Strategies in Patients with Fibromyalgia - Ji-Young Song; Samuel Noh; Manfred Harth; Harold Merskey (Pain Research and Management)
OBJECTIVE: To explore the hypothesis that the intensity of pain, pain thresholds and coping mechanisms differ between patients with fibromyalgia and those with rheumatoid arthritis (RA) in order to determine whether pain coping strategies contribute to the understanding of how patients adjust to fibromyalgia.